A Narrative Enquiry of Experienced Family Carers of People with Dementia Volunteering in a Carer Supporter Programme. (17th February 2014) - Brooks, Alice; Farquharson, Lorna; Burnell, Karen; Charlesworth, Georgina
ABSTRACT Whilst positive and negative aspects of general volunteering have been noted in the literature, little is known about the experience of volunteering to provide peer support to carers of people with dementia. The present study explored the impact of participating in a carer supporter programme in the context of previous caring experiences. Eight carer supporters, who had participated in the programme for at least 5 months, took part in semi‐structured interviews to elicit rich, extended narratives of their experiences. Narrative analysis of the interview transcripts covered structural, thematic and wider socio‐cultural components. The results indicated that most carer supporters naturally reflected on the positive impact of having shared experiences with the newer carers. Emotional and practical gains from participating in the programme were highlighted, as well as a greater sense of connection with others, extending to a wider social and organisational network. However, carer supporters also reflected on the negative emotions that could be evoked. The findings of the study indicate that the carer supporter role has potential to facilitate new roles, activities and social identities, but participation needs to be considered in relation to potentially stressful transitional points throughout the caring career. Role definition issues also need further consideration. Copyright © 2014 John Wiley & Sons, Ltd.